1, 8-Naphthalimide-based dual-response fluorescent probe for highly discriminating detection of cys and H2S. (February 2020) - Li, Kai-Bin; Qu, Wang-Bo; Shen, Qiongxia; Zhang, Siqi; Shi, Wei; Dong, Lei; Han, De-Man
Abstract: Hydrogen sulfide (H2 S) and cysteine (Cys) are ubiquitous biological thiols in physiological and pathological processes of living systems. Their aberrant concentration levels are associated with many diseases. Hence, we developed a water-soluble fluorescent (FL) probe for H2 S and Cys response. The probe was synthesized by two steps of reaction coupling between a triethylene glycol naphthalimide dye and 7-chlorobenzofurazan-4-sulfonyl chloride (CBD) dye linked by a rigid piperazine group. The probe displayed dual fluorescence emission for Cys (λem = 571 nm) and H2 S (λem = 535 nm) detection, accompanied by different absorbance changes for Cys (λex = 405 nm) and H2 S (λex = 486 nm). The probe could distinguish Cys and H2 S from other biological thiols (GSH, Hcy) with longer wavelength or stronger fluorescence emission. Moreover, the probe was allowed to sense the exogenous or endogenous H2 S and Cys with dual-emission signal (blue and red channel) in living MCF-7 cells. Highlights: A water-soluble fluorescent probe for discriminating detection of H2 S and Cys. The probe displayed dual fluorescence emission for Cys and H2 S detection. Allowed to sense the exogenous or endogenous H2 S and Cys in living cells.